식품으로 인한 유해물질 노출평가를 위한 설문지 개발 - 신상아(Shin, Sangah); 최슬기(Choi, Seul Ki); 김혜미(Kim, Hyemi); 이경윤(Kyung Youn); 신상희(Shin, Sanghee); 이정원(Lee, Jung Won); 유수현(Yu, Soo Hyun); 남혜선(Nam, Hye-Soen); 윤혜정(Yoon, Hae-Jung ); 정효지(Joung, Hyojee) (Hanʼguk yongyang hakhoe chi, 2011)
The aim of this study was to develop a reliable dietary questionnaire to assess human exposure to food-borne hazards. Eleven food-borne hazards were chosen as a priority control list through a literature review and advisory committees. The 11 food-borne hazards were phthalate, aflatoxin, bisphenol A, polycyclic aromatic hydrocarbons, dioxin, polychlorinated biphenyls, mercury, lead, cadmium, arsenic, and acrylamide. The characteristics, exposure level, and paths of these hazards were reviewed, and questionnaire items were identified to assess human exposure from the literature. A questionnaire was developed for each selected food based on its characteristics. Based on the items in the individual questionnaires, a comprehensive questionnaire, which contained demographic characteristics, job information, socioeconomic factors, health related lifestyles, and dietary behaviors, was developed. A 99-item food frequency questionnaire (FFQ) to assess food-borne hazard exposure was also developed. The FFQ included frequency of food intake during the previous year, container type for purchasing and storing food, and cooking method. The questionnaire developed in this study could be applied to assess dietary factors during an exposure assessment of food-borne hazards in a large population. A validation study for the questionnaire is needed before applying it to surveys. 본 연구는 유해물질 인체 노출 요인의 가장 큰 부분을 차지하는 식생활에 대한 과학적이고, 유해물질 인체 노출 조사 결과의 신뢰성을 높일 수 있는 표준화된 설문지를 개발하는 것이다. 본 연구의 결과를 요약하면 다음과 같다. 1) 본 연구에서는 문헌고찰 및 자문회의를 통해 식품으로인한 유해물질 노출의 대상물질을 11종 선정하였다. 11개 유해물질은 프탈레이트, 아플라톡신, 비스페놀A, PAHs, 다이옥신, PCBs, 수은, 납, 카드뮴, 비소, 아크릴아마이드를 선정하였다. 2) 선정된 유해물질별로 종류와 특성을 파악하고, 식품을 통한 노출 수준, 노출방법, 노출경로 등을 조사하였다. 유해물질별로 노출 특성을 반영하여 선정된 11개의 유해물질 노출평가를 위한 공통 설문 문항을 도출하였다. 3) 11개의 유해물질 노출평가를 위한 설문지를 토대로 통합적인 설문지를 개발하였다. 개발한 식생활 조사지는 인구학적 특성, 직업 특성, 사회경제적 특성, 건강 관련 특성, 식품 섭취 행태 관련 문항을 포함하였다. 식품섭취행태를 조사하기 위해 19개의 식품군을 세분화하여 총 99개의 식품목록으로 개발하였고, 지난 1년간 섭취한 식품의 빈도와 구매시 주로 사용하는 용기, 보관시 주로 사용하는 용기, 주로 사용하는 조리방법에 대한 질문을 포함하였다. 이상의 연구 결과를 토대로 본 연구에서 개발한 식품으로 인한 통합적 유해물질 노출평가 설문 조사지를 이용하여 우리 국민의 유해물질 노출 수준을 파악하고, 위험 집단을 선별하는 연구 수행을 실시할 수 있을 것이다. 이를 통해 유해물질 노출관리를 위한 정책 수립을 위한 기초 자료를 생산할 수 있다는데 그 의의가 있다.